Diagnosa Penyakit Kelenjar Teroid Menggunakan Metode Case Based Reasoning - Rizky Ramadan; Magdalena Simanjuntak; Suci Ramadani (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Thyroid gland disease is a disorder that affects the thyroid gland, which plays a vital role in regulating the body's metabolism. Common symptoms associated with thyroid disease include tremors, concentration difficulties, changes in the menstrual cycle, and neck enlargement. At RSUD Dr. RM. Djoelham, Binjai, many patients struggle to understand and diagnose this disease early due to a lack of information and specific symptoms. To address this issue, an information technology-based system is needed to help the public recognize thyroid disease symptoms and provide an early diagnosis. One effective approach for designing such a system is using Case Based Reasoning (CBR), a method based on experience that solves problems by finding similar cases from existing data. This system can process symptoms entered by users, such as dry skin, anxiety, neck enlargement, and others. Based on previous cases, the system will calculate the percentage probability of the disease, thereby providing a more accurate early diagnosis. For example, if the selected symptoms are dry skin, neck enlargement, and shortness of breath, the system can give a 42% probability of a thyroid gland disorder.